Relationship between internet addiction and dependency virtual social networks with loneliness in adolescents - Bibi Aghdas Asghari (Gonabad University of Medical Sciences, 2018)
The prevalence rate of harmful use of cyberspace in the world is constantly increasing. This means that those who are addicted to the Internet, experience negative consequences of it, such as feeling of loneliness and isolation, and a vicious circle as well as a bilateral relationship may be involved. In this paper we studied the relationship between online social network dependency and internet addiction with loneliness in Gonabad adolescents. The statistical population consisted of all adolescents in the range of 13-20 years in Gonabad city. Samples have been selected just among high school students because of the easy accessibility. The participants includes 568 boys and girls students in 9, 10 and 11 grades of high school. Three questionnaires were the Internet Addiction Test (IAT), University of California, Los Angeles Loneliness Scale and researcher-made questionnaire of virtual social network dependency. The results showed that the rate of intense addiction to internet among Gonabadian adolescents (8.8%) is lower compared to the prevalence of internet addiction among Iranian adolescents (10.24%). Also the mean of loneliness is nearly 40 and 16.9% (98 individuals) of the participants have earned scores higher than the mean of loneliness and 83.1% of adolescents had score lower than the mean of loneliness. Data shows that there is very weak direct and significant statistical relationship between internet addiction and loneliness and between virtual social network dependency and loneliness. The results showed that but adolescents did not feel emotional loneliness and severe social isolation despite the dependence on modern media tool is elusive from society and need for privacy (away from other people)